Invocation by Rational Evidence (Islamic Sciences Journal, 2023)
If the function of the theology is to study the belief rulings brought by Islamic Sharia as being the foundations upon which all other rulings are based, then it must depend on the evidences transmitted from the Prophet (peace and blessings of Allah be upon him) - whether it was Qur’an or a prophetic hadith - as the transmitter of the Islamic law. This does not mean turning away from the rational evidence that reveal the truth corresponding to what is included in the transmission, as long as the Sharia has commanded the use of reason and urged each individual to think and contemplate.
Keywords: protest, mental evidence The science of speech, the paths of protes ,.